TERRITORY, WORK AND WORKER'S HEALTH: A NECESSARY APPROACH - Perpetua, Guilherme Marini [UNESP]; Heck, Fernando Mendonca; Thomaz Junior, Antonio [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2018)
In the last few decades, important overcoming efforts from disciplinary trenches have been implemented in different learning areas, like the Geography cases, the labor studies and the health sciences. In this context, this paper aims to highlight the space dimension of the worker's health, proposing an approach of dialecticalmaterialist bias centered in the territory concept focused in reveal unseen traits of the domination and capitalist exploration and its corollary, the precariousness and the work degradation in different places and labor activity sectors. In methodological terms, we appealed, fundamentally, to the bibliography review in different sources and areas of knowledge, featuring Geography and the worker's health.
Keywords: Territory; work; worker's health; labor injuries